Describing the Level of Awareness of Micro-Enterprises in Local Taxation - Paul Cezam Rivera; Allene Kyle Mirrar; Mark Nicole Malazarte (TIJAB (The International Journal of Applied Business))
Background: Local taxes play a vital role in contributing significant socio-economic development and welfare in the city. This paper describes the level of awareness of micro-enterprises in local taxation.